Tendencias da mortalidade infantil, perinatal e seus componentes em Campinas : 1971 a 1999 - Carvasan, Gislaine Aparecida Fonsechi (2002)
Orientadores: Carlos Roberto Silveira Correa, Maria do Rosario Dias de Oliveira Latorre